The Role of Digital Literacy in Information Discernment and Misinformation Resilience: A Dual-Outcome Analysis in the Nigerian Social Media Context - ESHIET, Glory Bassey (Àgídìgbo: ABUAD Journal of the Humanities, 2025)
This study investigates the relationship between digital literacy and misinformation resistance among Nigerian social media users, examining both information discernment capability and misinformation resilience behaviour as distinct outcomes. Through a quantitative survey of 306 active social media users in Nigeria, the research employs PLS-SEM to analyse the direct and mediated relationships between these variables. The study demonstrates strong positive relationships between digital literacy and fact-checking behaviour (β = 0.681, p < 0.001), and between fact-checking behaviour and both information discernment capability (β = 0.609, p < 0.001) and misinformation resilience behaviour (β = 0.428, p < 0.001). These results suggest that the development of practical verification skills, rather than general digital competencies alone, is crucial for effective misinformation resistance. The findings contribute to our understanding of how digital literacy influences misinformation resistance in developing nations and provide practical implications for digital literacy education programs and social media platform policies.